Concise enantioselective synthesis of 1-[(S)-3-(dimethylamino)-3,4 dihydro-6,7-dimethoxyquinolin-1(2H)-yl]propan-1-one, (S)-903 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2009)
A concise enantioselective synthesis of (S)-903, an inotropic agent, is described in nine linear steps and 95% ee based on asymmetric dihydroxylation of cinnamate ester and Co-catalyzed Multifunctional reduction of several functional groups leading to the construction of core tetrahydroquinolin-3-ol, as the key steps. (C) 2009 Elsevier Ltd. All rights reserved.

Co(III)(salen)-catalyzed HKR of two stereocentered alkoxy- and azido epoxides: a concise enantioselective synthesis of (S,S)-reboxetine and (+)-epi-cytoxazone - Reddy, R. Santhosh; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Chavan, Vilas B.; Sudalai, Arumugam (Chemical Communications, 2010)
The HKR of racemic syn- or anti- alkoxy- and azido epoxides catalyzed by Co(salen) complex affords a practical access to a series of enantioenriched syn- or anti- alkoxy- and azido epoxides and the corresponding 1,2-diols. This strategy has been successfully employed in the concise, enantioselective synthesis of bioactive molecules such as (S, S)-reboxetine and (+)-epi-cytoxazone.

Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones

CN-assisted oxidative cyclization of cyano cinnamates and styrene derivatives: a facile entry to 3-substituted chiral phthalides - Reddy, R. Santhosh; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2012)
The asymmetric dihydroxylation (AD) of o-cyano cinnamates and styrene derivatives leads to efficient construction of chiral phthalide frameworks in high optical purities. This unique reaction is characterized by unusual synergism between CN and osmate groups resulting in rate enhancement of the AD process. The method is amply demonstrated by the synthesis and the structural/stereochemical assignment of the natural products.

Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays

CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.